HUBTINGAN POLA ASUH ORANGTUA DENGAN STATUS KEBERSIHAN GIGI DAN MULUT PADA SISWA TUNANETRA - Dwi Rahayu; Isnanto - (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
Dental health is part of overall health. Dental health status of one person can beknoown from teeth and oral hygiene. Based on preliminary data retrieval can be known low status of oral hygiene in Class V and VI SDLB A YPAB Surabaya. Therefore, how to maintain oral hygiene right to know the children at an early age, including children with disabilities (blind). Parenting of porents become one of the important factors in status of oral hygiene is good. The purpose of this study was to determine the relationship of parenting porents with status of oral hygiene in grade V and Vl SDLB A YPAB Surabaya. Type of study is a cross sectional analytic with the target number of 20 students (dependent variable) and 20 mothers of students (independent variables), methods of data collection used is the examinotion of dental and oral hygiene status and distribution of questionnaires to the student's mother, a date analysis technique using chi square and presented in tabular form. From the research that has been carried out it was concluded that there was no relationship between parenting parents with dental and oral hygiene status of blind studens in grade V and VI SDLB A YPAB Surabaya.